TIME ASSESSMENT IN CLASSICAL VS DIGITAL IMPRESSIONS - Andreea Codruța Novac; Vlad Filip; Daria Negruț; Ioana Moldovan; Daniela Maria Pop; Alina Tănase; Cristian Zaharia; Emanuela Lidia Crăciunescu; Meda Lavinia Negruțiu; Mihai Rominu; Virgil-Florin Duma; Cosmin Sinescu (Romanian Journal of Oral Rehabilitation, 2023)
Aim of the study is an ex-vivo time analysis comparing conventional and digital impression methods for prosthodontic restorations. Insights gleaned from ex-vivo experiments hold promise for enhancing existing practices. This primary experimental investigation will prioritize the consideration of both clinician and patient requirements when determining treatment modalities. Materials and Method: The study involved five stages: preparing an artificial arch, measuring time for gingival retraction with cords and paste, assessing time for conventional and digital impressions, and data analysis. A Frasaco maxillary model with 16 teeth was utilized, 14 prepared using cylindrical-conical burs. Gingival retraction cords and paste were applied, and impression times were recorded for both conventional and digital methods. Results and Discussions: Time analyses showed varying durations for gingival retraction techniques, with the paste method significantly faster than retraction cords. Digital impressions exhibited shorter scanning times compared to conventional methods, especially for fewer number of teeth. However, conventional two-step impressions took longer but provided better cervical area fidelity. This study highlighted the efficiency of digital scanning, offering shorter impression times and reduced patient discomfort. Research also emphasized the differences between retraction methods, with varied effects on periodontal tissues and impression quality. Comparison studies indicated benefits and challenges associated with different impression techniques. Conclusion: The findings underscored the need for practitioners to choose impression methods based on time efficiency and patient needs. Optical scanning proved quickest for fewer teeth, while retraction cord and paste methods require careful consideration. While the study didn’t explore gingival tissue effects, it highlighted crucial considerations for impression materials and chemical solutions. These insights offer practitioners guidance in selecting optimal techniques for effective and efficient dental procedures.